Selenium reduces acrylamide-induced testicular toxicity in rats by regulating HSD17B1, StAR, and CYP17A1 expression, oxidative stress, inflammation, apoptosis, autophagy, and DNA damage. - Cinar, İrfan; Yıldırım, Serkan; Gelen, Volkan; Aksu, Emrah Hicazi; Şengül, Emin; Tekin, Samet; Dag, Yusuf (My University, 2024)
This study investigated the effects of Selenium (Se) on testis toxicity induced by Acrylamide (ACR) in rats. In our study, 50 male adult rats were used, and the rats were divided into five groups; control, ACR, Se0.5 + ACR, Se1 + ACR, and Se1. Se and ACR treatments were applied for 10 days. On the 11th day of the experimental study, intracardiac blood samples from the rats were taken under anesthesia and euthanized. Sperm motility and morphology were evaluated. Dihydrotestosterone, FSH, and LH levels in sera were analyzed with commercial ELISA kits. MDA, GSH, TNF-α, IL-6, and IL-1β levels and SOD, GPx, and CAT, activities were measured to detect the level of oxidative stress and inflammation in rat testis tissues. Expression analysis of HSD17B1, StAR, CYP17A1, MAPk14, and P-53 as target mRNA levels were performed with Real Time-PCR System technology for each cDNA sample synthesized from rat testis RNA. Testicular tissues were evaluated by histopathological, immunohistochemical, and immunofluorescent examinations. Serum dihydrotestosterone and FSH levels decreased significantly in the ACR group compared to the control group, while LH levels increased and a high dose of Se prevented these changes caused by ACR. A high dose of Se prevented these changes caused by ACR. ACR-induced testicular oxidative stress, inflammation, apoptosis, changes in the expression of reproductive enzymes, some changes in sperm motility and morphology, DNA, and tissue damage, and Se administration prevented these pathologies caused by ACR. As a result of this study, it was determined that Se prevents oxidative stress, inflammation, apoptosis, autophagy, and DNA damage in testicular toxicity induced by ACR in rats.
Keywords: Male; Inflammation; Acrylamide; Dihydrotestosterone; Apoptosis; Antioxidants; Rats; Selenium; Oxidative Stress; Testis; Sperm Motility; Autophagy; Animals; Follicle Stimulating Hormone; DNA Damage